ANALYSIS OF COMMUNITY EMPOWERMENT IN TOURISM VILLAGES THROUGH DIGITALIZED EDUCATION AND CULTURAL TOURISM PROMOTION IN BALI PROVINCE - Sanjaya, I Gede Wahyu; Ananda, Nyoman; Agung, I Gusti Ngurah Pertu; Putra, Anggara Putu Dharma (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2025)
This study examines the role of digital empowerment in strengthening community participation within Bali’s culture-based tourism villages. Using a qualitative descriptive approach supported by quantitative data from the Bali Provincial Tourism Office (Disparda, 2025), the research analyzes 505 tourism attractions categorized by type—natural, cultural, and artificial—and by compliance with tourism standardization criteria. Results indicate that only 20.2% of attractions are compliant, highlighting significant disparities in digital readiness and management quality. Gianyar and Badung Regencies show higher preparedness for digital promotion, while Buleleng, Klungkung, and Karangasem require focused efforts in digital literacy and content creation. The study’s novelty lies in integrating quantitative indicators of tourism feasibility with qualitative assessments of digital education and empowerment. By linking compliance data with community digital capacity, the findings offer strategic insights for policymakers and tourism stakeholders. The study concludes that advancing digital skills and literacy among local tourism actors is essential for fostering sustainable, inclusive, and culturally grounded digital tourism development in Bali.